Praktik Rasial di Amerika Serikat Bagian Selatan pada Tahun 1960 an di Film Mississippi Burning : Sebuah Analisis Wacana Kritis - Arrasyid, M. Fauzi; Syam, Essy; Mohd. Fauzi (UIN Alauddin Makassar, 2022)
This study analyzes racial practices in the movie Mississippi Burning, which portrays racism in the Deep South of America in the 1960s. This study used Jäger and Meier's Critical Discourse Analysis (CDA) and a descriptive qualitative method, which explains and reveals racial practices in the Deep South through Jim Crow Law and the Ku Klux Klan in the 1960s. This study's analysis data are the scenes depicting racism in the Deep South collected from the Mississippi Burning movie and the explanation of these pictures based on Jäger and Meier's CDA. After that, these data were analyzed by selecting and reducing it in finding racial practices in the Deep South, categorizing the data based on non-discursive practices with a table, and drawing a conclusion from the analysis. This study shows that Whites engaged in racial practices such as segregation, violence, lynching, intimidation, and burning Black churches. The Whites used these racial practices in this movie had the purpose of upholding Jim Crow Law, White supremacy, and preventing blacks from the vote and their advancement in larger communities.